(untitled) (International Journal of Studies in Nursing, 2019)
This study examined the knowledge and experiences regarding the execution of sexual health care, as well as the sexual self-concepts, of nursing students and their effects on students’ competency in providing sexual health care in general hospitals. This was a cross-sectional study in which data was collected from 428 nursing students attending nursing schools in Northern Taiwan. Data was gathered using a self-administered questionnaire which collected information on demographic characteristics, sexual self-concept, sexual health care knowledge, skills, and experiences. The results showed that an average of 81.2% of the items in the sexual health care knowledge and skills scale were answered correctly. Although the students’ did not have sexual anxiety, they reported mild negative self-evaluations of their sexual consciousness, and uncertainty regarding sexual needs and activities. The variables of receiving sexual health care training, experiences of sexual harassment, sexual self-concept, knowledge of sexual health care, and experiences of the execution of sexual health care were able to effectively explain 66% of the variation in competency in providing sexual health care. Moreover, students’ previous experiences of the execution of sexual health care (β=.784, p<.0001) were found to have the strongest influence on their competency in providing sexual health care. This study showed that nursing students’ competence in providing sexual health care in hospitals requires participation, engagement in, and the accumulation of practical care experience in order to develop sexual health care competencies and establish a positive caring attitude.